2016
DOI: 10.1021/acs.jchemed.6b00045
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on “YouTestTube.com”: An Online Video-Sharing Platform To Engage Students with Chemistry Laboratory Classes

Abstract: This paper describes the construction and development of YouTestTube.com, a YouTube clone website to facilitate video sharing, social networking, and reflection of chemistry laboratory classes for year one students within the School of Biomedical Sciences at Ulster University. The practice was first introduced in the 2008/09 academic year and has developed until the present time. We reflect on our findings with regard to the production and sharing of short student-generated video documentaries on laboratory ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…The authors had experiences trying several replacement strategies and found the following options that faculty might explore if e-learning persists as the default mode of teaching from the Fall of 2020. First, we substituted large-class review sessions by prerecording video presentations using video recording software and uploaded on LumiNUS. For synchronous learning, we tried live streaming via online platforms such as YouTube and Facebook. For small-group discussions, we used the breakout rooms on Zoom. This is especially important for flipped courses such as CM1121 .…”
Section: Substitutes For F2f Teaching Practicementioning
confidence: 99%
“…The authors had experiences trying several replacement strategies and found the following options that faculty might explore if e-learning persists as the default mode of teaching from the Fall of 2020. First, we substituted large-class review sessions by prerecording video presentations using video recording software and uploaded on LumiNUS. For synchronous learning, we tried live streaming via online platforms such as YouTube and Facebook. For small-group discussions, we used the breakout rooms on Zoom. This is especially important for flipped courses such as CM1121 .…”
Section: Substitutes For F2f Teaching Practicementioning
confidence: 99%
“…Though technology can be adapted for online teaching and learning, F2F classroom teaching better provides a teacher–student interaction for improved student learning outcomes. , This is because F2F classroom teaching provides a social context and immediate feedback to the students on subject matter topics they are learning. , However, online teaching offers flexibility in learning and helps low-confidence learners via a variety of platforms for studying and learning. Therefore, applying both methods of teaching (blended learning) could enhance student learning through the creation of an engaging environment. ,, …”
Section: Introductionmentioning
confidence: 99%
“…While the mean comfort level for the virtual presentation was slightly lower, consistent with the lack of experience (Figure A), >80% of students indicated a comfort level of at least 3 (moderate comfortability) for either format. This perceived comfortability with the virtual presentation format, even without prior experience in a course project, can be attributed to current students’ everyday exposure to and “informal” training with video producing and uploading to sites such as YouTube. , While some students may still prefer a more traditional project format, students’ propensity for social media and new technologies generally instills a high level of confidence when tasked with communicating via a video presentation in a new setting.…”
Section: Resultsmentioning
confidence: 99%